Γ″ variant-sensitive deformation behaviour of Inconel 718 superalloy. (1st November 2022) - Zhang, R.Y.; Qin, H.L.; Bi, Z.N.; Tang, Y.T.; Araújo de Oliveira, J.; Lee, T.L.; Panwisawas, C.; Zhang, S.Y.; Zhang, J.; Li, J.; Dong, H.B.
Highlights: This study reveals, for the first time, the micro-mechanism of deformation of γ″ strengthened superalloys using neutron diffraction. Inconel 718 samples with different γ″ variant distributions were prepared by different stress ageing heat treatments. The γ″ variant-sensitive deformation behavior was studied by interpreting the stress-lattice strain curves. Compressive-aged sample shows larger yield strength compared to the tensile-aged sample The difference in strengthening arises from the interactions between dislocations and different γ″ variants. Abstract: Strengthening in Inconel 718 superalloy is derived from dislocation interaction with γ″ precipitates, which exist in disk-shaped three possible orientation variants with their {100} habit plane normal to each other. The interactions between dislocations and γ″ precipitates vary according to the γ″ orientation variants, which makes the deformation behaviour complicated and difficult to reveal experimentally. In this work, γ″ variant distributions of Inconel 718 samples were tailored by ageing heat treatment under either tensile or compressive stress. The γ″ variant-sensitive deformation behaviours were then studied by in situ tensile tests via neutron diffraction at room temperature. It is demonstrated that yielding first takes place in grains oriented with <110> parallel to the loading direction. An identical lattice strain response to applied stress of both the γ matrix and the γ″ precipitates was observed during yielding, suggesting that dislocations shearing through the γ″ precipitates is predominant at this stage. Variations in yield strength for samples with different γ″ variant distributions were observed, which can be attributed to different strengthening that arises from interactions between dislocation and different γ″ variants.